Chemerin Regulates Epithelial Barrier Function of Mammary Glands in Dairy Cows - Yutaka Suzuki; Sachi Chiba; Koki Nishihara; Keiichi Nakajima; Akihiko Hagino; Won-Seob Kim; Hong-Gu Lee; Tomonori Nochi; Toru Suzuki; Sang-Gun Roh (Animals, 2021)
Epithelial barrier function in the mammary gland acts as a forefront of the defense mechanism against mastitis, which is widespread and a major disorder in dairy production. Chemerin is a chemoattractant protein with potent antimicrobial ability, but its role in the mammary gland remains unelucidated. The aim of this study was to determine the function of chemerin in mammary epithelial tissue of dairy cows in lactation or dry-off periods. Mammary epithelial cells produced chemerin protein, and secreted chemerin was detected in milk samples. Chemerin treatment promoted the proliferation of cultured bovine mammary epithelial cells and protected the integrity of the epithelial cell layer from hydrogen peroxide (H2O2)-induced damage. Meanwhile, chemerin levels were higher in mammary tissue with mastitis. Tumor necrosis factor alpha (TNF-α) strongly upregulated the expression of the chemerin-coding gene (RARRES2) in mammary epithelial cells. Therefore, chemerin was suggested to support mammary epithelial cell growth and epithelial barrier function and to be regulated by inflammatory stimuli. Our results may indicate chemerin as a novel therapeutic target for diseases in the bovine mammary gland.